A new species of Wallinia Pearse, 1920 (Digenea: Allocreadiidae) collected from Astyanax fasciatus (Cuvier, 1819) and A. lacustris Lucena and Soares, 2016 (Characiformes: Characidae) in Brazil based on morphology and DNA sequences - Dias, Karina G. A. [UNESP]; Müller, Maria I. [UNESP]; de Almeida, Aline C. [UNESP]; da Silva, Reinaldo J. [UNESP]; de Azevedo, Rodney K.; Pérez-Ponce de León, Gerardo; Abdallah, Vanessa D. (Springer Nature, 2018)
Wallinia brasiliensis n. sp. is described from the intestine of two species of tetras—Astyanax fasciatus (Cuvier, 1819) and Astyanax lacustris Lucena and Soares, 2016—collected from the Batalha River in São Paulo State, Brazil. The new species can be clearly distinguished from the other three congeneric species by its vitelline follicles extending from the genital pore to the end of the caeca, eggs lacking operculum, a larger egg size with a consequently lower number relative to the other three species, and the ovary located opposite the anterior testis. The validity of the new species was confirmed through a phylogenetic analysis of the 28S rRNA gene which showed that the new species is the sister taxon to Wallinia mexicana Pérez-Ponce de León, Razo-Mendivil, Mendoza-Garfía, Rubio-Godoy and Choudhury, 2015, a species infecting Astyanax mexicanus (De Filippi, 1853) in Mexico.
Keywords: 28S rDNA; Astyanax fasciatus; Astyanax lacustris; South America; Wallinia